INOVASI PENA SETAJAM PEDANG DI DINAS KEARSIPAN DAN PERPUSTAKAAN PASAMAN BARAT - Isna Ahmad, Nur; Desriyeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to collect information regarding the evaluation of integrated archives management reaching regional and village apparatuses in the Archives and Library Service of West Pasaman Regency. The descriptive method that will be used aims to explain the variables and objects studied with data obtained in the field using theories that have been studied so that conclusions can be drawn from the data obtained. The results of the study indicate that integrated archives management reaching regional and village apparatuses in the Archives and Library Service of West Pasaman has a very high level of effectiveness contextually, effectiveness in the input aspect is considered quite adequate, and support in the form of Regent Regulations and commitment of the leadership of the Archives Service is a major strength. The implementation of innovation through the “jemput bola” method or direct mentoring has proven effective in transferring archival knowledge to the Nagari apparatus. As well as product evaluation is very effective, tangible results are seen from the creation of a systematic archive search list and an increase in the speed of archive retrieval.